A Survey of Methods for Achieving Efficiency in Electricity Consumption - P., Ozoh; S., Abd-Rahman; Jane, Labadin (Foundation of Computer Science FCS, New York, USA, 2016)
This paper investigates related research work on electricity consumption in buildings and outlines its context relative to improving efficiency in appliance usage by customers. The aim of this research is to study the impact of applying powersaving measures on appliance usage in order to reduce electric costs. The study focuses on a review of tools and methods involved in achieving efficient electricity consumption system with respect to minimization of electric costs and reduction of electricity wastage in the system. It also conducts a survey of various literatures involving the potential impact of incorporating power-saving measures on low-power and highpower appliances to allow for more efficient use of electrical appliances. The paper provides a number of recommendations for achieving efficiency in electricity consumption, when power-saving measures are applied to appliance usage.